2002
DOI: 10.1097/00004647-200203000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Striking Differences in Glucose and Lactate Levels between Brain Extracellular Fluid and Plasma in Conscious Human Subjects: Effects of Hyperglycemia and Hypoglycemia

Abstract: Brain levels of glucose and lactate in the extracellular fluid (ECF), which reflects the environment to which neurons are exposed, have never been studied in humans under conditions of varying glycemia. The authors used intracerebral microdialysis in conscious human subjects undergoing electrophysiologic evaluation for medically intractable epilepsy and measured ECF levels of glucose and lactate under basal conditions and during a hyperglycemia-hypoglycemia clamp study. Only measurements from nonepileptogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
148
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 204 publications
(169 citation statements)
references
References 68 publications
19
148
0
2
Order By: Relevance
“…Moreover, while estimates of lactate concentrations using magnetic resonance spectroscopy in normal human brain (which includes intra-and extracellular fluid) are between Ͻ0.03 and 1 mmol/l (32), recent more direct measurements of lactate in brain extracellular fluid (ECF) in rodents and human subjects by microdialysis show a much different picture. Lactate levels in the brain ECF are three-to fivefold higher than plasma (28). In comparison, brain interstitial glucose concentrations, measured by microdialysis are estimated to be ϳ25-30% systemic glucose levels (28).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Moreover, while estimates of lactate concentrations using magnetic resonance spectroscopy in normal human brain (which includes intra-and extracellular fluid) are between Ͻ0.03 and 1 mmol/l (32), recent more direct measurements of lactate in brain extracellular fluid (ECF) in rodents and human subjects by microdialysis show a much different picture. Lactate levels in the brain ECF are three-to fivefold higher than plasma (28). In comparison, brain interstitial glucose concentrations, measured by microdialysis are estimated to be ϳ25-30% systemic glucose levels (28).…”
Section: Discussionmentioning
confidence: 96%
“…Specifically, both in vivo and in vitro studies suggest that lactate is readily utilized as a substrate for neurons when glucose is deficient (19,20,25,26). While blood levels of lactate and its transport across the blood-brain barrier appear not to be the major source of lactate supply to the brain (24,27,28), it has been reported that lactate is produced locally in brain by astrocytic nonoxidative glucose metabolism during neuronal activation (29,30). In keeping with this hypothesis, local stimulation of brain tissue in vivo produces a rise in brain interstitial lactate concentration in the absence of changes in systemic lactate levels (31).…”
Section: Discussionmentioning
confidence: 99%
“…A Neurobasal-A media, devoid of glucose and pyruvate (NB-A f ), allowed for the control of glucose concentrations. We supplemented NB-A f with B27 and either a non-physiological high glucose concentration of 25 mM (NB-A 25 ), or 3 mM (NB-A 3 ), a physiological glucose concentration for the brain (Silver, et al, 1994;Abi-Saab, et al, 2002;de Vries, et al, 2003) (Fig. 1A).…”
Section: Restorative Feedings Reduce Fluctuations In Ambient Glucose mentioning
confidence: 99%
“…Extracellular glucose concentrations in rodent and human brain are closely coupled to plasma glucose concentrations (Silver, et al, 1994;Abi-Saab, et al, 2002;de Vries, et al, 2003). In euglycemia, plasma glucose can range from 5.5 to 7.8 mM, while brain glucose fluctuates from 0.82 to 2.4 mM, depending on the microdialysis method employed (Silver, et al, 1994;Abi-Saab, et al, 2002;de Vries, et al, 2003). Using glucose microelectrodes to continuously monitor changes in glucose concentrations it has been demonstrated that the extracellular glucose concentration in the brain is altered dramatically during hyper-and hypoglycemia, in which plasma levels may reach 15.2 mM or drop to 2.8 mM, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, a 'normal' physiological plasma glucose concentration (5-7 mM) correlates with a brain extracellular glucose concentration of approximately 2 mM, by invasive microdialysis studies [1,17,27], resulting in a linear 3:1 ratio between plasma and tissue glucose concentrations [27]. Plasma glucose concentrations of <3 mM lead to impaired cognitive function [3,4], and limitations of glycolysis [17,18].…”
Section: Comparison Of In Vitro Glucose Ambient Levels and In Vivo CLmentioning
confidence: 99%